Study protocol: randomized controlled trial of manualized components in home visitation to reduce mothers' risk for child maltreatment - Merel de Wit; Patty Leijten; Claudia van der Put; Jessica Asscher; Merian Bouwmeester-Landweer; Maja Deković (BMC, 2020)
Abstract Background This study tests whether home visitation to prevent child maltreatment can be improved by adding manualized program components, targeting four key risk factors for child maltreatment: low parental self-efficacy, high levels of perceived stress, parental anger, and post-traumatic stress symptoms. Home visitation is widely implemented, but effects on child maltreatment risk tend to be modest at best. Home visitation tends to be rather flexible (i.e., professionals decide how to support each family). We will test whether adding manualized program components increases program effectiveness, by ensuring that key risk factors are addressed, while maintaining flexibility. In addition, we will test whether any component effects on reduced child maltreatment risk can be explained (i.e., is mediated) by ameliorated risk factors. Lastly, we will test whether the components are more effective for some mothers (e.g., those at highest child maltreatment risk) than for others. Methods We will conduct a randomized controlled trial among 398 mothers enrolled in a Dutch home visiting program targeting families at risk for child maltreatment. Mothers in the experimental group will receive the manualized components in two consecutive home visits, while mothers in the control group will receive regular home visits (care as usual). Mothers will fill out questionnaires at four time points: before and after each of the two home visits. Outcome variables include the four targeted risk factors parental self-efficacy, perceived stress, parental anger, and (recognition of) post-traumatic stress symptoms, as well as parenting practices (e.g., rejection and affection), and risk for child maltreatment. Discussion This study aims to determine whether adding manualized program components to a flexible home visiting program increases program effectiveness on risk for child maltreatment. In addition, our test of whether the effects of the components on risk for child maltreatment is explained (i.e., mediated) by amelioration of the targeted risk factors, may contribute to our understanding of the role of these risk factors in child maltreatment. Our tests of which mothers benefit most from adding the components may help move the field towards evidence-based personalized family support. Trial registration This trial has been retrospectively registered in the Netherlands Trial Register (NL8005).